Chiral Brønsted Acid‐Catalyzed Asymmetric Synthesis of N‐Aryl‐cis‐aziridine Carboxylate Esters. (24th April 2017) - Bew, Sean P.; Liddle, John; Hughes, David L.; Pesce, Paolo; Thurston, Sean M.
Abstract: We report a multi‐component asymmetric Brønsted acid‐catalyzed aza‐Darzens reaction which is not limited to specific aromatic or heterocyclic aldehydes. Incorporating alkyl diazoacetates and, important for high ee's, ortho‐tert‐butoxyaniline our optimized reaction (i.e. solvent, temperature and catalyst study) affords excellent yields (61–98 %) and mostly >90 % optically active cis‐aziridines. (+)‐Chloramphenicol was generated in 4 steps from commercial starting materials. A tentative mechanism is outlined.